Pengaruh Terapi Musik Terhadap Lama Persalinan Kala 1 Fase Aktif di Puskesmas Maja Desa Maja Kecamatan Maja Kabupaten Lebak Banten - Ricky Riyanti; Nur Ismi Wahyuni (Malahayati Nursing Journal, 2024)
ABSTRACT Prolonged childbirth as a cause of maternal death also tends to be quite high. Lebak Regency long parturition is one of the causes of 59 cases of maternal death. One effort to speed up the delivery process is to provide music therapy. Music therapy is a form of distraction so that the patient can relax, which can speed up the delivery process. Knowing the effect of music therapy on the length of labor in the first active phase at the Maja Community Health Center, Maja Village, Maja District, Lebak Regency, Banten. Quasi-experimental design with posttest only design with control group design The sample was made up of mothers who gave birth at the Maja Health Center in Maja Village, Maja sub-district, Lebak district, Banten, in March–May 2023, with a total of 30 samples using a purposive sampling technique. The intervention was given for 30 minutes. Bivariate analysis used the independent t-test. The results of the univariate study showed that the duration of labor in the first active phase in the intervention group with music therapy averaged 155.33 minutes, while the average duration of labor in the first active phase in the control group was 214.80 minutes. The results of the bivariate study showed the effect of music therapy on the length of labor in the first active phase with a p value of 0.000. There is an effect of music therapy on the length of labor in the first active phase. It is expected that health workers provide services to mothers in childbirth in an effort to improve the quality of midwifery services for mothers in childbirth, especially to reduce labor pain and speed up the delivery process, one of which is by using music therapy in order to improve the quality of midwifery services in the progress of maternal labor. Keywords: Music Therapy, Active Phase 1 Period of Labor  ABSTRAK Persalinan lama sebagai salah satu penyebab kematian ibu juga cenderung cukup tinggi. Kabupaten Lebak partus lama menjadi salah satu penyebab dari 59 kasus kematian ibu. Salah satu upaya untuk mempercepat proses persalinan adalah dengan memberikan terapi musik. Terapi musik merupakan bentuk distraksi agar pasien dapat rileks sehingga dapat mempercepat proses persalinan. Mengetahui pengaruh terapi musik terhadap lama persalinan kala 1 fase aktif di Puskesmas Maja Desa Maja Kecamatan Maja Kabupaten Lebak Banten. Quasi eksperimental desain dengan rancangan posttest only with control groups design. Sampel adalah ibu bersalin yang melahirkan di Puskesmas Maja Desa Maja kecamatan Maja kabupaten Lebak Banten pada bulan Maret-Mei 2023 sejumlah 30 sampel dengan teknik purposive sampling. Intervensi diberikan selama 30 menit. Analisis bivariat menggunakan uji T-test Independent. Hasil penelitian univariat lama persalinan kala I fase aktif pada kelompok intervensi pemberian terapi musik rata-rata 155,33 menit, lama persalinan kala I fase aktif pada kelompok kontrol rata-rata 214,80. Hasil penelitian bivariat terdapat pengaruh terapi musik terhadap lama persalinan kala 1 fase aktif dengan nilai p = 0,000. Terdapat pengaruh terapi musik terhadap lama persalinan kala 1 fase aktif. Diharapkan tenaga kesehatan dalam memberikan pelayanan pada ibu bersalin dalam upaya peningkatan kualitas pelayanan kebidanan pada ibu bersalin terutama untuk mengurangi nyeri persalinan dan mempercepat proses persalinan salah satunya dengan menggunakan terapi musik agar dapat meningkatkan mutu pelayanan kebidanan pada kemajuan persalinan ibu. Kata Kunci: Terapi Musik, Lama Persalinan Kala 1 Fase Aktif